2022
DOI: 10.1021/acsami.2c12123
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Ni–Ru Bimetallic Catalyst Integrated with MFI Zeolite-Loaded Cerium Zirconium Oxide for Dry Reforming of Methane

Abstract: The dry reforming of methane (DRM) is a new potential technology that converts two major greenhouse gases into useful chemical feedstocks. The main challenge faced by this process is maintaining the catalyst with high catalytic activity and long-term stability. Here, a simple and effective preparation route for the synthesis of functional nanomolecular sieve catalysts (NiRu x CZZ5) from kaolinite tailings was developed for dry reforming of methane with CO 2 . The silica monoliths with flower-like spherical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…The authors found that the sturdy SiO 2 ‐Ru interaction, along with the confinement effect of the silica shells, which hampered Ru migration, decreased the gathering of Ru particles at the high reaction temperature (700 °C), also inhibiting carbon generation. Miao and co‐workers [268] reached an outstanding catalytic activity and stability (at 800 °C and GHSV of 60,000), over 100 h of reaction, with initial CO 2 and CH 4 conversions of 100 % and 100 %, and final CO 2 and CH 4 conversions of 78 % and 68.8 %, respectively, using a NiRu x CZZ5 catalyst, composed by a flower‐like spherical ZSM‐5 zeolite with metal components loaded by ultrasonic‐assisted impregnation method. Beyond the ability of Ru atoms to slow down CH 4 dissociation and increase C* oxidation, such findings accounted for the interfacial confinement of microporous molecular sieves and the strong metal‐support interaction guaranteed by the unique morphology of the ZSM‐5 zeolite, providing high sintering resistance.…”
Section: Dry Reforming Of Methanementioning
confidence: 99%
“…The authors found that the sturdy SiO 2 ‐Ru interaction, along with the confinement effect of the silica shells, which hampered Ru migration, decreased the gathering of Ru particles at the high reaction temperature (700 °C), also inhibiting carbon generation. Miao and co‐workers [268] reached an outstanding catalytic activity and stability (at 800 °C and GHSV of 60,000), over 100 h of reaction, with initial CO 2 and CH 4 conversions of 100 % and 100 %, and final CO 2 and CH 4 conversions of 78 % and 68.8 %, respectively, using a NiRu x CZZ5 catalyst, composed by a flower‐like spherical ZSM‐5 zeolite with metal components loaded by ultrasonic‐assisted impregnation method. Beyond the ability of Ru atoms to slow down CH 4 dissociation and increase C* oxidation, such findings accounted for the interfacial confinement of microporous molecular sieves and the strong metal‐support interaction guaranteed by the unique morphology of the ZSM‐5 zeolite, providing high sintering resistance.…”
Section: Dry Reforming Of Methanementioning
confidence: 99%
“…[ 1 ] DRM has been regarded as a promising route to tackle excess greenhouse gas emissions as it converts the two greenhouse gases of CO 2 and CH 4 to syngas (H 2 and CO), a key chemical feedstock for large‐scale industrial processes to produce fuels, high‐value‐added chemicals, and clean hydrogen energy. [ 2–26 ] However, there are two major obstacles to this scenario. One is high energy consumption for DRM as it is a highly endothermic reaction (Δ H 298 = 247 kJ mol −1 ), requiring a high reaction temperature (usually above 700 °C).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2–6,27–46 ] Intensive studies have identified metallic Ni‐based catalysts as the most promising candidate for both conventional thermocatalytic and light‐driven catalytic DRM owing to their earth‐abundance, inexpensiveness, and high initial activity comparable to precious metal catalysts. [ 9–14,18–34 ] However, they are vulnerable to deactivation due to severe coking, blocking their widely practical application. As the side reactions of coking are thermodynamically unavoidable, [ 12,13 ] the key issue of the catalyst deactivation could only be tackled through rationally designing unique Ni‐based catalysts that could kinetically inhibit coking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al explored that the strong acid sites on ZSM-5 facilitated the conversion of syngas to aromatics, but too strong Brønsted acidity can lead to side reactions that reduce the selectivity of aromatics. Moreover, the strong support interaction and reduced carbon deposition contributed mainly to the improved catalytic activity. , …”
Section: Introductionmentioning
confidence: 99%